THE CONTINUING EFFECTS OF TECHNOLOGICAL PROGRESS ON AGRICULTURE FARMERS - Tejbahadur, Singh Atish; B. P. Bhol (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The impression of technology on agriculture comprises various fields, such as fertilizers, pesticides, seed technical developments, and more. New advances in the field of bioengineering and genetic alteration have led to increased pest resistance and enhanced crop production. The implementation of machinery has resulted in improved cultivating and harvesting processes, as well as a noteworthy decrease in the need for manual labor. The developments in methods of irrigation and infrastructure for transportation, coupled with the reduction of waste generated by industrial machinery, are clearly observable across various sectors. The variety of soil microorganisms is disrupted by agricultural technologies such as pesticides and land clearing, despite the fact that soil microbes play an essential part in the recycling of nutrients. It is possible for agrochemicals to cause contamination of the air, water, and eutrophication when they are used in excessive amounts. By 2050, predictions specify that the global population will reach 9 billion, a situation that will likely present challenges associated with the reduction of agricultural land and the problem of food waste. Technology possesses the capacity to assist in addressing these challenges, consequently diminishing foreign exchange losses, augmenting productivity, and improving the livelihoods of farming communities. Despite the considerable distance India must traverse to fully embrace contemporary agricultural methods, there exists an urgent necessity to enlighten farmers regarding the benefits of such practices. To forge a more promising future, it is imperative to transcend the confines of outdated mindsets and archaic traditions. The integration of technology within the agricultural sector holds the promise of transforming India into a self-sufficient nation, reducing its dependence on external resources.